2014
DOI: 10.7189/jogh.04.020401
|View full text |Cite
|
Sign up to set email alerts
|

Community case management of childhood illness in sub–Saharan Africa – findings from a cross–sectional survey on policy and implementation

Abstract: BackgroundCommunity case management (CCM) involves training, supporting, and supplying community health workers (CHWs) to assess, classify and manage sick children with limited access to care at health facilities, in their communities. This paper aims to provide an overview of the status in 2013 of CCM policy and implementation in sub–Saharan African countries.MethodsWe undertook a cross–sectional, descriptive, quantitative survey amongst technical officers in Ministries of Health and UNICEF offices in 2013. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 15 publications
(15 reference statements)
3
85
0
Order By: Relevance
“…Variable immunization coverage in Ethiopia has led to recommendations to address regional variations in service delivery and access to information [66]. We observed that measles and DPT-3 immunization coverage is generally lower in more remote areas of west and central Africa, possibly indicating poor access to services, while the band of high-high coverage in eastern Africa may be related to ease of access to services and cultural acceptance.…”
Section: Discussionmentioning
confidence: 82%
“…Variable immunization coverage in Ethiopia has led to recommendations to address regional variations in service delivery and access to information [66]. We observed that measles and DPT-3 immunization coverage is generally lower in more remote areas of west and central Africa, possibly indicating poor access to services, while the band of high-high coverage in eastern Africa may be related to ease of access to services and cultural acceptance.…”
Section: Discussionmentioning
confidence: 82%
“…7 uptake of iCCM by national governments in Africa has been rapid, increasing from a total of 7 countries with iCCM policies in 2005 to 28 countries by 2013. [11] The scale-up of community-based delivery platforms, including treatment of the common causes of child deaths, has contributed to the achievement of MDG4 in several countries in Africa, including Malawi and Niger. [12,13] SA embarked on a strategy to re-engineer the primary healthcare (PHC) system in 2011, including the creation of ward-based out reach teams (WBOTs), comprising approximately six CHWs supervised by one nurse.…”
Section: Corresponding Author: T Doherty (Tanyadoherty@mrcacza)mentioning
confidence: 99%
“…In 2014, only 27 of 42 sub-Saharan African countries surveyed were providing "complete" iCCM compared with 35 providing CCM for diarrhea and 32 for malaria. 17 A recent meta-analysis showed that one of the most important aspects of scalable interventions with CHWs is community acceptance. 18 Although some studies have demonstrated that iCCM interventions are acceptable to the community, 19,20 others have shown that programs are resisted if CHWs do not provide services of value.…”
Section: Introductionmentioning
confidence: 99%